Technical Assessment of an Automated Treatment Planning on Dose Escalation of Pancreas Stereotactic Body Radiotherapy. (19th July 2019) - Wang, Shuo; Zheng, Dandan; Lin, Chi; Lei, Yu; Verma, Vivek; Smith, April; Ma, Rongtao; Enke, Charles A.; Zhou, Sumin
Background: Stereotactic body radiotherapy has been suggested to provide high rates of local control for locally advanced pancreatic cancer. However, the close proximity of highly radiosensitive normal tissues usually causes the labor-intensive planning process and may impede further escalation of the prescription dose. Purpose: The present study aims to evaluate the consistency and efficiency of Pinnacle Auto-Planning for pancreas stereotactic body radiotherapy with original prescription and escalated prescription. Methods: Twenty-four patients with pancreatic cancer treated with stereotactic body radiotherapy were studied retrospectively. The prescription is 40 Gy over 5 consecutive fractions. Most of patients (n = 21) also had 3 other different dose-level targets (6 Gy/fraction, 5 Gy/fraction, and 4 Gy/fraction). Two types of plans were generated by Pinnacle Auto-Planning with the original prescription (8 Gy/fraction, 6 Gy/fraction, 5 Gy/fraction, and 4 Gy/fraction) and escalated prescription (9 Gy/fraction, 7 Gy/fraction, 6 Gy/fraction, and 5 Gy/fraction), respectively. The same Auto-Planning template, including beam geometry, intensity-modulated radiotherapy objectives and intensity-modulated radiotherapy optimization parameters, were utilized for all the auto-plans in each prescription group. The intensity-modulated radiotherapy objectives do not include any manually created structures. Dosimetric parameters including percentage volume of PTV receiving 100% of the prescription dose, percentage volume of PTV receiving 93% of the prescription dose, and consistency of the dose-volume histograms of the target volumes were assessed. Dmax and D1 cc of highly radiosensitive organs were also evaluated. Results: For all the pancreas stereotactic body radiotherapy plans with the original or escalated prescriptions, auto-plans met institutional dose constraints for critical organs, such as the duodenum, small intestine, and stomach. Furthermore, auto-plans resulted in acceptable planning target volume coverage for all targets with different prescription levels. All the plans were generated in a one-attempt manner, and very little human intervention is necessary to achieve such plan quality. Conclusions: Pinnacle 3 Auto-Planning consistently and efficiently generate acceptable treatment plans for multitarget pancreas stereotactic body radiotherapy with or without dose escalation and may play a more important role in treatment planning in the future.